2010
DOI: 10.1016/j.transproceed.2010.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation in a Randomized Controlled Trial of Emergency Treatment of Acutely Bleeding Esophageal Varices in Cirrhosis

Abstract: Background Bleeding esophageal varices (BEV) in cirrhosis has been considered an indication for liver transplantation (LT). This issue was examined in a randomized controlled trial (RCT) of unselected, consecutive patients with advanced cirrhosis and BEV that compared endoscopic sclerotherapy (EST) (n=106) to emergency direct portacaval shunt (EPCS) (n=105). Methods Diagnostic workup and treatment were initiated within 8 hours. Patients were evaluated for LT on admission and repeatedly thereafter. 96% underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…We examined the issue of liver transplantation as part of our trial of emergency treatment of BEV, and in addition, we analyzed our results regarding liver transplantation in 1300 nonrandomized patients in whom we previously performed portacaval shunt beginning in 1978. 35 The results of our study indicate that liver transplantation is seldom required following control of bleeding by portacaval shunt. If recurrent BEV is prevented, as was true in 100% of the portacaval shunt patients, both randomized and nonrandomized, prolonged survival occurs, equal to or better than survival following liver transplantation.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…We examined the issue of liver transplantation as part of our trial of emergency treatment of BEV, and in addition, we analyzed our results regarding liver transplantation in 1300 nonrandomized patients in whom we previously performed portacaval shunt beginning in 1978. 35 The results of our study indicate that liver transplantation is seldom required following control of bleeding by portacaval shunt. If recurrent BEV is prevented, as was true in 100% of the portacaval shunt patients, both randomized and nonrandomized, prolonged survival occurs, equal to or better than survival following liver transplantation.…”
Section: Resultsmentioning
confidence: 63%
“…Screening for HCC by ultrasonography every 6 months was done according to the consensus recommendation of the American Association for the Study of Liver disease 21 and the European Association for the Study of the Liver. 35 The screening for HCC by AFP determinations monthly for the first postentry year and every 3 months thereafter was more frequent than that recommended by consensus. Regrettably, there are no reports in the literature that describe a more effective surveillance program for detecting HCC in cirrhotic patients with BEV.…”
Section: Resultsmentioning
confidence: 98%
“…Despite the fact that only a small fraction of cirrhosis patients with bleeding will ultimately undergo liver transplantation after the TIPS placement (3–10% in most series), an unsubstantiated belief that those patients will be candidates for possible liver transplant has resulted in the adoption of the TIPS as the decompressive shunt of choice and as a bridge to transplant by clinical decision makers. In a randomized controlled trial (RCT) reported by Orloff (MJ) et al ., which compared endoscopic sclerotherapy with emergency PSS in 211 unselected consecutive patients with advanced cirrhosis and bleeding oesophageal varices, only 6% were referred for OLT and only 2% underwent OLT, with worse 1‐ and 5‐year survival rates . In addition, this analysis was supplemented by 1300 non‐randomized cirrhosis patients who previously underwent SSPCS with 100% follow‐up, of whom only 3.8% were referred for and only 1.5% actually underwent OLT, again with a worse 5‐year survival rate …”
Section: Discussionmentioning
confidence: 99%
“…However, there is good reason to propose that these findings are applicable to patients undergoing elective treatment of BEV. In point of fact we examined the issue of alcoholic versus nonalcoholic cirrhosis in an unrandomized study of 1300 patients who underwent direct portacaval shunts for BEV, 700 electively and 600 as an emergency [19]. We found no differences between alcoholics and nonalcoholics in any of the outcome parameters including control of bleeding, survival, PSE and effect on liver function.…”
Section: Discussionmentioning
confidence: 99%